Translation Analysis of Idiomatic Phrasal Verbs found in Fleabag series season 1 - Mariska Puspita Ningrum (Universitas Sebelas Maret, 2024)
This research discusses the translation of idiomatic phrasal verbs found in Fleabag series season 1. The purposes of this research are to identify the types of idiomatic phrasal verbs, analyze the translation strategies applied in translating the idiomatic phrasal verbs, and assess the quality of translation of idiomatic phrasal verbs in Fleabag series season 1 in terms of accuracy and acceptability.The results of this research are in the following order: firstly, there are three types of idiomatic phrasal verbs discovered in the series. 71,25% of the data are dominated by inseparable idiomatic phrasal verb. Subsequently, there are only three translation strategies applied by the translator in the series. These translation strategies include translation by paraphrase (71 data), using an idiom of similar meaning but dissimilar form (7 data), and using an idiom of similar meaning and form (2 data). The analysis of the quality of translation shows that most of the translations receive high score in both aspects. The average score for the accuracy is 2.85, while for the acceptability is 2.96. This result indicates that the translations of idiomatic phrasal verbs in Fleabag series season 1 are considered as accurate and acceptable.